2010
DOI: 10.1007/bf03326142
|View full text |Cite
|
Sign up to set email alerts
|

Role of metal species in flocculation rate during estuarine mixing

Abstract: Flocculation can be considered as an effective mechanism in self-purification of metals during estuarine mixing. In the present investigation, flocculation of metals during mixing of Minab River water with the Strait of Hormuz (The Persian Gulf) water is studied for the first time. Flocculation behavior of metals (except for Pb) is governed by dissolved organic carbon. The source of dissolved organic carbon is terrigenous in the estuarine waters of study area. The general pattern of flocculation of studied met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
13
0
3
Order By: Relevance
“…The accumulation of organic substances can both affect the quality of reservoir water and change the oxidation state into anoxic condition. Reduction condition together with low pH will cause mobilization of metals to upper water levels (Biati et al, 2010). This may lead to serious changes in the water quality of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of organic substances can both affect the quality of reservoir water and change the oxidation state into anoxic condition. Reduction condition together with low pH will cause mobilization of metals to upper water levels (Biati et al, 2010). This may lead to serious changes in the water quality of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Redox potential is of major concern for mobilization of trace metals in estuaries where an oxygen gradient exists in addition to the salinity gradient (Gerringa et al, 2001). Besides, this studies showed that similar to the findings of Biati et al (2010b) mechanisms for flocculation of Pb is still unknown and further investigations is needed to find out governing factors in the flocculation of Pb. Moreover, Karbassi et al (2008b) stated that pH and PO 4 control flocculation of Cu in Babolrud estuarine process.…”
Section: Resultsmentioning
confidence: 54%
“…This is in accordance with the findings of other researchers (Duinker and Nolting, 1978 Biati et al (2010a). Biati et al (2010b) showed that pH, temperature, DO, alkalinity, HCO 3 , CO 3 , EC, salinity, Na, Cl, Mg, SO 4 and Ca do not have any role on the flocculation process during mixing of the Minab River water with the Persian Gulf waters. Redox potential might have reverse effect in flocculation process in Minab estuary.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Karbassi et al (2010) showed that flocculation rate in the strait of Hormouz (connection between The Persian Gulf and Sea of Oman) is in the order of Cu(83.3%)> Ni(82.9%)> Zn(75.5%)> Mn(69.4%)> Pb(38%) [24]. Figure 2 shows the results of cluster analysis of the data.…”
Section: Resultsmentioning
confidence: 99%